What's wrong with Obamamania? : Black America, Black leadership, and the death of political imagination - Jones, Ricky L. (State University of New York Press, 2008)
"In What's Wrong with Obamamania?, Ricky L. Jones places Obama's run for the presidency in the context of deep and often disturbing shifts in black leadership since the 1960s. From Charles Hamilton Houston to Thurgood Marshall to Jesse Jackson, from prosperity preachers to megachurches, from W.E.B. DuBois's Talented Tenth and civil rights advocates to Black Entertainment Television and hip-hop culture, Jones paints a picture of lowered expectations, cynicism, and nihilism that should give us all pause."--Jacket